2005
DOI: 10.1002/ep.10104
|View full text |Cite
|
Sign up to set email alerts
|

Reaction kinetics for the degradation of phenol and chlorinated phenols using Fenton's reagent

Abstract: Fenton's reaction is an advanced treatment technol-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 36 publications
2
9
0
Order By: Relevance
“…However, further increase in the substrate concentration from 500 to 1,000 mg/L provided a degradation efficiency of 94 and 72 %, respectively, after 90 min of irradiation. These results correspond closely to other similar reported work (De et al 2006). Decreasing of degradation efficiency at high concentration may be attributed to the consumption of Fenton reagent before oxidation process completed.…”
Section: Effect Of Irradiation Time and Initial Concentrationsupporting
confidence: 93%
“…However, further increase in the substrate concentration from 500 to 1,000 mg/L provided a degradation efficiency of 94 and 72 %, respectively, after 90 min of irradiation. These results correspond closely to other similar reported work (De et al 2006). Decreasing of degradation efficiency at high concentration may be attributed to the consumption of Fenton reagent before oxidation process completed.…”
Section: Effect Of Irradiation Time and Initial Concentrationsupporting
confidence: 93%
“…A similar study was reported by Anotai et al (2006). De et al (2006) studied degradation of phenol and chlorinated phenols. Quite a few studies were reported on the degradation of residual dyes and dyeing wastewater using the Fenton's reagent.…”
supporting
confidence: 59%
“…Fenton systems in particular have been found to be very active for the oxidation of 2-chlorophenol (2-CP), and as a result these have been well-studied [2][3][4]. In the case of heterogeneous Fenton systems, goethite (a-FeOOH) has been shown to catalyze the oxidation of 2-chlorophenol in the presence of hydrogen peroxide [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%